2013
DOI: 10.1002/pbc.24493
|View full text |Cite
|
Sign up to set email alerts
|

Risk adopted allogeneic hematopoietic stem cell transplantation using a reduced intensity regimen for children with thalassemia major

Abstract: Implementing a risk-adopted therapy in patient with thalassemia in Jordan can result in an excellent thalassemia free and OS, especially in those at highest risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 16 publications
2
25
0
Order By: Relevance
“…11 Subsequently, several centers worldwide have started their own transplant programs. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] Recent results show that, with modern transplantation approaches, and careful patient selection, even better results could be obtained (Table 2). At the same time, however, survival without transplantation of TM patients has improved as the result both of a better understanding of the pathophysiology of iron overload and improvements in the medical therapy of TM; survival into the fourth or fifth decade of life is now possible for well-treated patients.…”
Section: Hsct In Children and Adolescentsmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Subsequently, several centers worldwide have started their own transplant programs. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] Recent results show that, with modern transplantation approaches, and careful patient selection, even better results could be obtained (Table 2). At the same time, however, survival without transplantation of TM patients has improved as the result both of a better understanding of the pathophysiology of iron overload and improvements in the medical therapy of TM; survival into the fourth or fifth decade of life is now possible for well-treated patients.…”
Section: Hsct In Children and Adolescentsmentioning
confidence: 99%
“…49,50 Although transplant-related toxicity was minimal, many patients showed only transient and incomplete engraftment, and most ultimately developed graft rejection, thus indicating that TM patients need a more intensive, myeloablative conditioning regimen (MAC). 29,51 However, to avoid the well-known late effects of radiotherapy on the growing organism, and in particular the risk of secondary malignancies, irradiation should not be an option for nonmalignant disorders. 52 A newer experience has shown that approximately 11% of transplanted patients develop long-term, stable mixed chimerism (MC) after HSCT.…”
Section: Conditioning Regimenmentioning
confidence: 99%
“…To reduce morbidity and mortality associated with myeloablative conditioning regimens, especially in patients with comorbidities, many investigators have developed and attempted to use reduced intensity conditioning (RIC) for several nonmalignant disorders (sickle cell disease, thalassemia, metabolic disorders) (Iannone et al, 2003;Hsieh et al, 2009;Anurathapan et al, 2013;Hussein et al, 2013). However, in these cases there were overall more instances of graft failures, more graftversus-host disease (GVHD), and a reduced proportion of disease-free survival in comparison with myeloablative regimens (Bernardo et al, 2012;Tolar et al, 2012;Galambrun et al, 2013;King and Shenoy, 2014).…”
Section: Introductionmentioning
confidence: 97%
“…35,36 Acute GVHD was described in 11% to 38% and chronic GVHD in 6% to 50% of MFD transplants depending on stem cell source (peripheral blood transplants had a higher GVHD risk than cord blood transplants), with a 15-year OS of 87% and DFS of 70% in MFD HSCT. 33,[37][38][39][40][41][42][43][44][45] With increasingly successful outcomes demonstrated, especially in patients with risk class I and II disease and lowered toxicity following modification in transplant methods, this curative treatment modality should be discussed with all patients with HLA-matched family members following establishment of diagnosis and transfusion dependency, usually by about 2 or 3 years of age.…”
Section: Thalassemia (Case 2)mentioning
confidence: 99%